The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s13762-022-04680-0
|View full text |Cite
|
Sign up to set email alerts
|

Review: CO2 capturing methods of the last two decades

Abstract: Due to the annual increase in CO2 emissions, climate change continues to progress. In order to achieve the goals set in the Paris Climate Agreement, CO2 capturing measures are necessary in addition to the reduction in carbon dioxide emissions. This review article describes and discusses the CO2 capturing methods published in the last 20 years. Processes for absorption, gas–solid reaction, adsorption, cryogenic processes, membrane processes and the capture of carbon dioxide with natural inclusion were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Further, the expression level of induced HepG2 cells in aggregates was significantly higher (≈1.7×) than in 2D culture. Taken together, these results confirmed that the HepG2 cell aggregates provided a beneficial culturing condition as previously reported for hepatocytes such as HepaRG [ 68–70 ] or primary human hepatocytes [ 66,71 ] when grown in spheroids. However, the present method of aggregate formation by rendering surfaces non‐adhesive with alginate, rather than producing single spheroids in, for example, ultra‐low attachment wells, presents an easy means of scaling up the production of aggregates.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Further, the expression level of induced HepG2 cells in aggregates was significantly higher (≈1.7×) than in 2D culture. Taken together, these results confirmed that the HepG2 cell aggregates provided a beneficial culturing condition as previously reported for hepatocytes such as HepaRG [ 68–70 ] or primary human hepatocytes [ 66,71 ] when grown in spheroids. However, the present method of aggregate formation by rendering surfaces non‐adhesive with alginate, rather than producing single spheroids in, for example, ultra‐low attachment wells, presents an easy means of scaling up the production of aggregates.…”
Section: Resultssupporting
confidence: 89%
“…CYP1A2 is one of the dominant enzymes of the CYP450 family that are involved in the phase I metabolism of the liver, [ 65 ] and is therefore an essential feature in the current effort. HepG2 cells are well known to have a limited inherent CYP1A2 activity compared to primary hepatocytes, [ 66 ] but the expression can be induced by treatment with the AhR agonist β‐napthoflavone (BNF). [ 67 ] The monitored production of resorufin by the HepG2 cells was normalized to the number of cells by quantifying the double‐stranded DNA (dsDNA, Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many industrial processes, improvements to the selective separation and storage of gases can yield significant advantages . For example, the separation of CO 2 from air (N 2 and O 2 ) or natural gas (CH 4 ) has been of long running interest in the energy industry. , Another example is the Haber–Bosch process in which ammonia must be separated from unreacted nitrogen and hydrogen gas. This is typically done through condensation of the product ammonia from the reactant gases; however, this process can be costly to set up and operate.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 can be captured either at the source of emission or from the atmosphere. [1][2][3][4] One way of accomplishing this is by capturing carbon dioxide using simple chemical reagents, usually acting as bases. For instance, amines (e.g.…”
Section: Introductionmentioning
confidence: 99%